GENDER EQUALITY ON NUSYUZ TREATMENT - Saidah, Filda Rahma; Khalfiah, Yuliani (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2022)
The nusyūz (spouse disobedience) treatment between husband and wife in daily marriage life has a significant differences. When it comes from the wife side, the treatment tends to provide a gap of violence through the stages of advice, separation of bed, and finally beatings/physical discipline which often became the reason of domestic violence. As for the husband, the treatment tends to be certain advices and even wife is encouraged to make peace by reducing a number of rights that need to be fulfilled by her husband. This inequality of nusyūztreatment on both sides seems to be biased and very detrimental to women. Perhaps this paper could offer a gender-based concept of nusyūz which could be an alternative in terms of the nusyūz treatment that occurs in both husband and wife. This library research uses the gender approach with descriptive analysis method. Finally, the result shows that (1) the classic nusyūz concept more focuses on the wife's disobedience rather than husband, (2) The understanding of nusyūz were changed with the changing social conditions starting from a) pre-Islamic Arab times, women did not have many rights and nusyūz had not become an intense topic, b) the arrival of Islam, women have a several rights and nusyūz were started to become a topic with a concept that tends to be patriarchal, and in modern ere the concept of nusyūz is still in its old meaning, and even tends to only be attached to wife. (3) the nusyūzsettlement steps based on an-Nisa (4): 34 could also be applied by the wife when her husband performs nusyūz.Keyword: Nusyūz; Gender; Treatment